2011
DOI: 10.1111/j.1439-0418.2011.01628.x
|View full text |Cite
|
Sign up to set email alerts
|

Field efficacy of Ceratitis capitata (Diptera: Tephritidae) mass trapping technique on clementine groves in Spain

Abstract: Mass trapping is being used in Mediterranean regions to control Ceratitis capitata (Wiedemann) (Diptera: Tephritidae) in citrus. The technique is based on placing a high density of traps with an attractant (Ferag CC D TM®, a three‐membrane dispensers of trimethylamine, ammonium acetate and diaminoalkane), and a toxicant, aiming to capture the highest numbers of adults in the grove. From 2006 to 2008, field trials were conducted in commercial Clementine (Citrus reticulata Blanco) groves to evaluate the efficacy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 29 publications
(46 reference statements)
4
29
0
1
Order By: Relevance
“…However, fruit damage was effectively avoided only with higher trap densities (75 or 100 traps/ha). These results are consistent with a later study (Martínez-Ferrer et al 2012) in which a unique dispenser with the blend of ammonium acetate, trimethylamine, and cadaverine was tested in the Probodelt trap. This study showed that a lower density of 25 traps/ha was sufficient to control damage in mid-season varieties (when pest pressure is low), whereas a higher density of traps was required for early-ripening varieties (when pest pressure is higher).…”
Section: Trap Density In Mass Trappingsupporting
confidence: 91%
See 3 more Smart Citations
“…However, fruit damage was effectively avoided only with higher trap densities (75 or 100 traps/ha). These results are consistent with a later study (Martínez-Ferrer et al 2012) in which a unique dispenser with the blend of ammonium acetate, trimethylamine, and cadaverine was tested in the Probodelt trap. This study showed that a lower density of 25 traps/ha was sufficient to control damage in mid-season varieties (when pest pressure is low), whereas a higher density of traps was required for early-ripening varieties (when pest pressure is higher).…”
Section: Trap Density In Mass Trappingsupporting
confidence: 91%
“…This finding can be attributed to the cumulative reduction in the fruit fly population that is associated with effective mass trapping. As higher trap densities entail higher costs, many authors (Leza et al 2008;Martínez-Ferrer et al 2012; suggest the combination of mass trapping and insecticide bait sprays as the most suitable strategy for growers in areas with high C. capitata populations. For example, Martínez-Ferrer et al (2012) performed field trials in 3 ha groves during three consecutive years.…”
Section: Factors Affecting Efficacy Of Mass Trappingmentioning
confidence: 99%
See 2 more Smart Citations
“…The advantages of mass trapping have been reported for Bactrocera oleae and C. capitata control . Those authors concluded that, under high pest density, mass trapping alone could not achieve sufficient control and bait sprays were necessary to reduce populations …”
Section: Discussionmentioning
confidence: 99%